PERAN MEDIASI MOTIVASI PADA PENGARUH DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR SANTI PALA - Putu Ayu Sintya Saraswati; Ary Wira Andika; Ni Wayan Ary Dian Laksmi (JUIMA : JURNAL ILMU MANAJEMEN, 2024)
The purpose of this study was to analyze the mediating role of motivation on the effect of work discipline and work experience on the performance of employees of PT BPR Santi Pala. This type of research uses quantitative research methods. The research population is employees of PT BPR Santi Pala, namely 38 employees who work at the company. Sampling using the saturated sample method using the SEM-PLS model. SmartPLS 4.0. Based on the results of hypothesis testing using SmartPLS, it shows that: Hypothesis 1 (H1) is accepted because the t-statistic value is 3.569> t-table 1.96 and the p-values are 0.000 <0.05. Hypothesis testing on H2 and H3 is also accepted because the p-values are smaller than 0.05. In addition, the mediation hypotheses H4 and H5 are accepted because the p-values are smaller than 0.05. Motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, work experience has a positive and significant effect on employee performance, motivation is able to mediate the effect of work discipline on employee performance, motivation is able to mediate the effect of work experience on employee performance.